Benefits from the adoption of genetically engineered innovations in the Ugandan banana and cassava sectors: an ex ante analysis - Kikulwe, Enoch Mutebi; Falck-Zepeda, José B.; Oloka, Herbert; Chambers, Judith A.; Komen, John; Zambrano, Patricia; Wood-Sichra, Ulrike; Hanson, Hillary (International Food Policy Research Institute, 2020)
The Government of Uganda has implemented programs and policies to improve the agricultural sector’s recent underperformance. Uganda’s two main food security crops, bananas and cassava, have been critically affected by two diseases: Banana Xanthomonas Wilt (BXW) and Cassava Brown Streak Disease (CBSD). The effectiveness of agronomic and cultural practices to control these diseases has been limited, requiring better alternatives. The Ugandan R&D sector in collaboration with international partners have developed genetically engineered innovations that can control both diseases. To examine the potential benefits to consumers and producers from the adoption of genetically engineered banana and cassava with resistance to BXW and CBSD, we use a set of economic impact assessment methods. These include an economic surplus model implemented via IFPRI’s DREAMpy framework, a real options model and a limited gender assessment. Results from the economic surplus approach suggest that the adoption of both technologies can benefit Uganda. These results were confirmed for the case of bananas and partially for the case of cassava using the real options and the gender assessment performed. Results from this assessment are predicated on Uganda maintaining an enabling environment that will ensure the deployment and use of both innovations. Looking forward, continuing to improve enabling environment for innovation in Uganda will require addressing current R&D, regulatory, technology deployment and product stewardship processes constraints.